Effectiveness Of William's Flexion Exercises In Management Of Low BackPain - Muhammad Usman Khalid; Mahvish Rafiq; Nosheen Zehra (ziauddin University, 2024)
ABSTRACT Background: Low back pain is a common musculoskeletal disorder affecting 84% people oncein third life time. It may be acute or chronic. Among various available options for management of low back pain, William's flexion exercise is one of them. William's flexion exercises the set of physical exercises use to enhance lumbar flexion to avoid lumbar extension, and strengthen the abdominal and gluteus musculature to manage low back pain Objective: To assessthe effectiveness of William flexion exercise in managementof patients with low back pain. Methodology: A cross sectional study was conducted among 250 patients with low back pain from different hospitals of Karachi. Sample was selected by convenience sampling technique and data wascollected on structured questionnaire. These patients were provided William's Flexion Exercise and changesin pain and posture were noticed before and after exercise. Data was analyzed by SPSS version 17and P value <0.05 was consideredas significant. Result: Pain intensity was significantly (p value = 0.03) reduced in those who took more than 5 sessions of William's Flexion Exercise. Of total 96 (38.4%) patients with severe pain before exercise, no Pain was found in 20 (8%) patients after exercise. From 107 (42.8%) and 47 (18.8%) patients with moderate and mild pain respectively, no pain was found in 9 (3.6%) and 11 (4.4%) patients respectively. Spine flexion and extension was improved completely in 45 (18%) outof 132 (52.8%) patients with mild restrictions, in 24 (9.6%) out of 93 (37.2%) patients with moderate restrictions and in 9 (3.6%) out of 25 (10%) patients with severerestrictions. Conclusion: William flexion exercise provided benefits to most of the participants in the study, thus it may be an effective technique to reducethe intensity of low back pain. Key Words: William's Flexion Exercise, Low Back Pain.